(3faMI GdbHhd aj eOM GdQShds - (3YHO GdZfj Hf ESeGYjd Hf YHO GdZfj GdfGHdSj,J (B1143 (3g` s ((3eMeO QTjO Hf GdTjN eMeO SYOj GdYeQj s)
(3ChdgG (B:s
(3CeG HYO, ajbhd GdTjN YHOGdZfj GdfGHdSj CjgG GdhGba Ydi gPG GdeLehY GdLGeY, hGdfhQ GdSGWY GddGeY s
(3BNQgG (B:s
(3CeO GdOgQ eG CVGA UHGM hHfaM GdYQGQ WGH YTi bO Je OjhGf GdeOjM s
(3GfXQ aj GdLRA GdChd JMJ Qbe (B310 (3COHs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B32s
Keywords: (3GdCOHs